Ta’zir Dalam Pidana Islam: Aspek Non Material - Vichi Novalia; Laudza Hulwatun Azizah; Novinda Al-Islami; Surya Sukti (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This article examines the issue of jarīmah ta'zīr as one of the dimensions of Islamic criminal law which has flexibility in its application. In contrast to ḥudūd and qisāṣ whose rules are very clear and detailed in the Qur'an, ta'zīr is not set clearly in the Qur'an. Therefore, the ijtihad of a ruler or judge to determine the type of crime and jarimah that can be punished (ta'zīr) and the type and form of punishment is really important. The flexibility of ta'zīr allows to accommodate the complex form of crime such as gratification, corruption, sexual harassment, drugs, and pornography. But ta'zīr also opens the opportunity for the tyranny of the government in punishing a person. This article offers the need for ta'zīr by making qanun like in Aceh.